IL-32: A Novel Pluripotent Inflammatory Interleukin, towards Gastric Inflammation, Gastric Cancer, and Chronic Rhino Sinusitis - Muhammad Babar Khawar; Muddasir Hassan Abbasi; Nadeem Sheikh (Mediators of Inflammation)
A vast variety of nonstructural proteins have been studied for their key roles and involvement in a number of biological phenomenona. Interleukin-32 is a novel cytokine whose presence has been confirmed in most of the mammals except rodents. The IL-32 gene was identified on human chromosome 16 p13.3. The gene has eight exons and nine splice variants, namely, IL-32α, IL-32β, IL-32γ, IL-32δ, IL-32ε, IL-32ζ, IL-32η, IL-32θ, and IL-32s. It was found to induce the expression of various inflammatory cytokines including TNF-α, IL-6, and IL-1β as well as macrophage inflammatory protein-2 (MIP-2) and has been reported previously to be involved in the pathogenesis and progression of a number of inflammatory disorders, namely, inflammatory bowel disease (IBD), gastric inflammation and cancer, rheumatoid arthritis, and chronic obstructive pulmonary disease (COPD). In the current review, we have highlighted the involvement of IL-32 in gastric cancer, gastric inflammation, and chronic rhinosinusitis. We have also tried to explore various mechanisms suspected to induce the expression of this extraordinary cytokine as well as various mechanisms of action employed by IL-32 during the mediation and progression of the above said problems.